Spontaneous remission of nephrotic syndrome associated with COVID-19 infection in an 8-year-old boy - Akyol, Aylin Kayalı; Dinç, Gamze Akça; Mustafaoğlu, Özlem; Yahşi, Aysun; Bayhan, Gülsüm İclal; Özlü, Sare Gülfem (The Turkish Journal of Pediatrics, 2022)
Background. It is already known that viral infections, exclusively upper respiratory tract infections may trigger relapses of nephrotic syndrome. Recently, COVID-19 disease has also been reported to be related with relapse of nephrotic syndrome in a few pediatric cases Case. Here we present an 8-year-old boy who had relapse of nephrotic syndrome due to COVID-19 infection. He was asymptomatic except for mild edema. He was managed supportively, no medication was started and went into spontaneous remission in 7 days. Conclusions. Viral infections particularly upper respiratory tract infections may trigger relapse of nephrotic syndrome. COVID-19 has also been reported to be related with relapses of nephrotic syndrome in a few pediatric cases. Spontaneous remission in our patient indicates the importance of close monitoring of patients before starting long term treatment with steroids.
Keywords: COVID-19; SARS-CoV-2; child; nephrotic syndrome